(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
The security policy of the Republic of Italy serves as a key framework for the realization of fundamental interests in the country. There is no doubt that Italy’s security policy has a specific place, given that it unites the country’s overall efforts to adequately respond to threats. Undoubtedly, this contributes to the formation of security measures, to the action of the security sector within the constitutionally permitted framework. At the same time, security policy enables political goals to grow into a political security doctrine that seeks to produce an optimal concept and strategy of action to achieve the set goals. The complexity, variability and interdependence of the security system and security policy is the reason why these two segments in Italy have been analysed in one place. The analysis is supported by many questions and analogous to many answers related to the creation of security policy and the conditions in which it is realized.